The Influence of Islamic Branding, Customer Testimonials and Cash On Delivery Services on Interest in Buying Muslim Fashion Through E-Commerce Shopee With Trust as a Moderating Variable - Magfira Annisa; Ayu Ruqayyah Yunus; Trisno Wardy Putra (IECON: International Economics and Business Conference, 2024)
An interesting phenomenon in the realm of muamalah is the existence of buying and selling transactions that occur through electronic media. One of them is the Shopee e-commerce which provides various needs and always provides attractive offers to its prospective consumers. This study discusses the interest in buying Muslim fashion through the Shopee e-commerce which experiences an imbalance between seeking product quality and conformity to Islamic values. The type of research used in this study is quantitative research, using the SEM (Structural Equation Modeling) analysis technique using a test tool, namely SmarPLS 4. The sampling method is based on the morgen table, respondents in this study amounted to 278 consumers. The results of the study showed that simultaneously the Islamic branding variables (X1), Customer testimonials (X2) and cash on delivery services (X3) have a positive and significant effect on the interest in purchasing (Y) Muslim fashion through the Shopee e- commerce. Meanwhile, trust (Z) as a moderator is unable to moderate the relationship between the three X variables and the Y variable.